2018
DOI: 10.1080/03043797.2018.1428531
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of cultural differences between American and Japanese mainstream science and engineering contexts from analysis of classroom discourse

Abstract: Teaching styles in science and engineering instruction were compared by analysing corpora of transcripts of lectures delivered in English and Japanese at leading universities in the United States and Japan, respectively. Our findings were compatible with cultural differences related to power distance and field dependence, which have been reported in the literature. Teaching styles seem to simultaneously result from the cultural context as well as reinforce it. Science and engineering instruction in the Japanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…These differences may be due to cultural differences and how participants may be educated in different geographical regions. Studies have shown differences in learning styles based on cultural background and this may have explained why differences in the estimated completion times between geographical regions were observed. These findings also highlight that the importance of being efficient depends on your location and may be related to differences in approaches taken in the delivery of analytical science in different countries.…”
Section: Exploring the Impact Of Geographical Regions On Expected Tim...mentioning
confidence: 99%
“…These differences may be due to cultural differences and how participants may be educated in different geographical regions. Studies have shown differences in learning styles based on cultural background and this may have explained why differences in the estimated completion times between geographical regions were observed. These findings also highlight that the importance of being efficient depends on your location and may be related to differences in approaches taken in the delivery of analytical science in different countries.…”
Section: Exploring the Impact Of Geographical Regions On Expected Tim...mentioning
confidence: 99%
“…The authors of [ 20 ] propose a model for analyzing student traces in the cloud. Teaching styles in the field of natural and technical sciences were compared by analyzing the totality of lecture transcripts in English and Japanese at leading universities in the USA and Japan, respectively [ 21 ]. Science and engineering education in the Japanese educational context tends to reflect and reinforce a teacher-centered personalized knowledge-style transfer that characterizes the field style of the Japanese cultural context and can reinforce this style among students, while teaching in the American context seeks to match and strengthen learning styles characterized by impersonal, inductive thinking, typical of the mainstream American culture.…”
Section: Problem Status: E-learning and Distance Study Toolsmentioning
confidence: 99%
“…Fruchter and Townsend (2003), for instance, designed an inclusive curriculum to accommodate the diversifying student body. Another trend is cross-cultural comparison studies of educational practices and values in either history or present days (Downey, et al, 2006;Zhou, et al, 2015;Kunioshi, et al, 2019). For instance, Downey and his colleagues (2006) discovered engineering education reformers in the U.S. focus on introducing design into engineering problem-solving, whereas European educators focus on preparing students for career mobility by restructuring degrees, expanding nontechnical contents and creating student-exchange programs.…”
Section: Research Of Culture Difference In Engineering Educationmentioning
confidence: 99%